PENGELOLAAN TANAH ADAT PADA MASYARAKAT ADAT BATAK TOBA DI KELURAHAN BARISAN PANCUR NAULI KOTA PEMATANG SIANTAR - Hendra Pranata; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Legal actions involving customary land that often occur are the pawn of customary land, Bataktoba indigenous people are more familiar with the term pawn. In this pate, traditional customary land canbe transferred to the owner even though the new owner is not from the inheritance line or a member of atraditional association (huta). The problem that often also occurs is when a family has ownership rightsover a customary land but the family does not have a lineage to inherit the customary land. If this happensto which party will receive from the ownership rights of the customary land. Of course this would be adebate among various parties in the village if the previous customary landowners did not give a will on therights of the customary land. Based on the background described above, the authors were interested inconducting research relating to the management of customary land to indigenous peoples. The title of theauthor was: